Perlindungan Hukum terhadap pembeli pada jual beli tanah dibawah tangan perspektif teori Maslahah Imam As-Syatibi: Studi Putusan Pengadilan Negeri Jombang, Nomor : 05/Pdt.G/2023/PN Jbg - Rahmah, Annisa Amelia (Maliki Interdisciplinary Journal, 2024)
The object of the sale and purchase of land rights which is carried out normatively underhand will be detrimental to the buyer because when the buyer registers the transfer of his rights (transfer of name) from the seller to the buyer to the Land Office, he will experience rejection by the local Land Office. This article will discuss the legal consequences and the legal force of transactions carried out both from a positive legal perspective and from the maslahah mursalah perspective of Imam Asy-Syatibi, and will discuss how legal protection is for buyers and what the judge’s considerations are in deciding the case. This research is a type of library research (normative), with a statutory approach (statue approach). The statutory approach is used with the aim of examining laws and regulations related to the issue being studied, which relies on secondary data sources consisting of primary legal materials, secondary legal materials and tertiary legal materials, which have a close relationship with the object research. The deed under the hand contains uncertainty. As long as there is no denial, its existence as a deed and evidence can have certainty and security. However, if there is a denial of the contents and signature, the certainty and security as a deed and evidence will be lost. In this case, mashlahah mursalah in a private land sale and purchase agreement can be carried out as long as it fulfills the sale and purchase requirements in muamalah law which provides benefits and avoids gharar. The deed under the hand in proving the existence of witnesses who justify in legal events because the legal force of the underhand agreement is not as strong as an authentic deed. There are two criteria made by al-Syatibi so that a mashlahah can be used as the basis for the formulation of Islamic law. First, the mashlahat must go hand in hand with the type of syara’ act, this is due to the mashlahat which does not go hand in hand with the shari’a act or violates the texts (al-Qur’an, Hadith, and Ijma’) being rejected as the basis for the formulation of Islamic law. Second, there is no specific argument that shows benefit in the first criterion.